Determinasi Knowledge Sharing Self-Efficacy, dan Kualitas Knowledge Sharing terhadap Employee Job Performance (Studi Pada PT. Aji Pangan Lestari) - Peni Indrawati (STIE Kertanegara Malang, 2022)
Disruption of digital technology that occurs as a result of the industrial revolution 4.0, demands development in various fields including the defense sector. The potential threats to the defense sector have extended even to the cybersecurity dimension. For this reason, it is necessary to develop information technology by involving stakeholders who have human resources with superior job performance. There are several factors that influence employee job performance in the defense sector, including the discussion on self-efficacy and knowledge sharing. Furthermore, this study aims to determine the effect of knowledge sharing self-efficacy and the quality of knowledge sharing on employee job performance. The research sample used is 45 employees of PT. Aji Pangan Lestari which is engaged in defense information technology. The data analysis method used is Partial Least Square using the SmartPLS 3.0 program. The results of the analysis show that the quality of knowledge sharing is largely determined by the knowledge sharing self-efficacy of employees. In addition, it is also concluded that knowledge sharing self-efficacy and the quality of knowledge sharing each have a significant effect on employee job performanceKeywords– knowledge sharing self-efficacy, quality of knowledge sharing, employee job performance